Reprogramming of the Developmental Program of Rhus javanica During Initial Stage of Gall Induction by Schlechtendalia chinensis - Hirano, Tomoko; Kimura, Seisuke; Sakamoto, Tomoaki; Okamoto, Ayaka; Nakayama, Takumi; Matsuura, Takakazu; Ikeda, Yoko; Takeda, Seiji; Suzuki, Yoshihito; Ohshima, Issei; Sato, Masa H. (Frontiers in Plant Science, 2020)
Insect galls are unique organs that provide shelter and nutrients to the gall-inducing insects. Although insect galls are fascinating structures for their unique shapes and functions, the process by which gall-inducing insects induce the formation of such complex structures is not well understood. Here, we performed RNA-sequencing-based comparative transcriptomic analysis of the early developmental stage of horned galls to elucidate the early gall-inducing process carried out by the aphid, Schlechtendalia chinensis, in the Chinese sumac, Rhus javanica. There was no clear similarity in the global gene expression profiles between the gall tissue and other tissues, and the expression profiles of various biological categories such as phytohormone metabolism and signaling, stress-response pathways, secondary metabolic pathways, photosynthetic reaction, and floral organ development were dramatically altered. Particularly, master transcription factors that regulate meristem, flower, and fruit development, and biotic and abiotic stress-responsive genes were highly upregulated, whereas the expression of genes related to photosynthesis strongly decreased in the early stage of the gall development. In addition, we found that the expression of class-1 KNOX genes, whose ectopic overexpression is known to lead to the formation of de novo meristematic structures in leaf, was increased in the early development stage of gall tissue. These results strengthen the hypothesis that gall-inducing insects convert source tissues into fruit-like sink tissues by regulating the gene expression of host plants and demonstrate that such manipulation begins from the initial process of gall induction.